KHOJA YUSUF HAMADANI IN THE MEMORY OF HIS CONTEMPORARIES AND FOLLOWERS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In this article, we attempted to evaluate the genius of Khoja Yusuf Hamadoni, a prominent representative of the Sufi world, based on the tazkiras, manoqibs, memoirs, and maqams written by his contemporaries, disciples, and followers.